Cultural criminology: some notes on the script (Delito y Sociedad, 2019)
In this paper the autors address some of the main characteristics of cultural criminology, a perspective that has had a remarkable development in recent years. Especially, they define the need for a new «cultural» approach in contemporary criminology for the Late Modernity, which forces us to rethink both its object and its research method. This proposal, that defines itself as novel, seek to trace its genealogy in approaches such as Matza’s «naturalism», Becker’s radical phenomenology or the critical perspective of the National Deviancy Conference, among others. In this way, the autors raise the need to dispute the criminological field with those «criminologies» that they call «positivists», «neoliberals» or «academics». Finally, they outline some examples of this «new/old» approach to criminology.
Keywords: Cultural Criminology; Late Modernity; Critical Criminology